More than 300 UMP volunteers help clean up flood waste - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 28 December 2021 - The post-flood volunteer activities that took place recently at Perumahan Awam Kos Rendah (PAKR) Sungai Pandan Taman Bukit Rangin Aman focused on cleaning in the house and the vicinity due to the pile of rubbish in front of the house which risks threatening the health of the residents.